2021
DOI: 10.1002/nop2.1040
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adverse events on patient outcomes in a Japanese intensive care unit: a retrospective observational study

Abstract: Adverse events (AEs) are defined as "unintended physical injury resulting from or contributed to by medical care that requires additional monitoring, treatment or hospitalization or that results in death (Griffin & Resar, 2009)." Diverse studies from various countries reported that AEs developed in 12% of hospitalized patients (Panagioti et al., 2019) while the severe and unstable patients often seen in the intensive care unit (ICU) experienced more AEs than those in other general wards (Andrews et al., 1997).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Multiple risk factors for PSEs have been reported, most notably in relation to delirium and prolonged hospital stay. 5,18,27,39 Although the postintervention had a high rate of mechanical ventilation, which has been identified as a risk factor for PSEs in several previous studies, 5,18,31,53 the current study found a low incidence of PSEs. Therefore, the collaborative 4:2 NCDS could possibly be effective even in a population at high risk for developing PSEs.…”
Section: Discussionmentioning
confidence: 44%
See 4 more Smart Citations
“…Multiple risk factors for PSEs have been reported, most notably in relation to delirium and prolonged hospital stay. 5,18,27,39 Although the postintervention had a high rate of mechanical ventilation, which has been identified as a risk factor for PSEs in several previous studies, 5,18,31,53 the current study found a low incidence of PSEs. Therefore, the collaborative 4:2 NCDS could possibly be effective even in a population at high risk for developing PSEs.…”
Section: Discussionmentioning
confidence: 44%
“…We determined the relationship between PSEs and length of stay and calculated the number of days spent in the EICU by examining the date of EICU admission and discharge. 5,18,31 Because staffing and bed occupancy rate (BOR) are also factors associated with PSEs, we investigated the number of nurses per shift, the number of patients admitted, and the number of available beds. 10,32 During the day shift (8:00-16:00), many nurses attend training and meetings, and it is difficult to assess how many nurses are involved in patient care retrospectively.…”
Section: Data Collection/measurementsmentioning
confidence: 99%
See 3 more Smart Citations